The prognostic role of Claudin 18.2 in advanced gastric or gastroesophageal junction adenocarcinoma: a systematic literature review - M. Fassan; I. Chau; H. Dasghaib; J. Hill; R. Pophale; K. Shitara (ESMO Gastrointestinal Oncology, 2025)
Claudin 18 isoform 2 (CLDN18.2) is a tight junction protein expressed in normal gastric tissue and retained in gastric or gastroesophageal junction (G/GEJ) adenocarcinoma. The phase III trials SPOTLIGHT and GLOW demonstrated improved survival following the addition of the CLDN18.2-targeted antibody zolbetuximab to chemotherapy. In this systematic literature review, we summarize existing evidence for the prognostic role of CLDN18.2 and association of CLDN18.2 with patient demographic and clinicopathological characteristics in patients with advanced G/GEJ adenocarcinoma. MEDLINE, Embase, clinical trials databases, and congress abstracts were searched for interventional and noninterventional studies that evaluated CLDN18.2 for patient/disease characteristics, survival, or expression of programmed death-ligand 1 as primary outcomes. Of 742 records identified, 18 publications (17 studies) were included. CLDN18.2 expression was not consistently associated with specific patient/disease characteristics in most studies; two studies reported an association of CLDN18.2 expression with Lauren classification but differed on its association with diffuse or intestinal histology. Most studies reported that CLDN18.2 expression was not a statistically significant prognostic factor; among those that reported CLDN18.2 as a prognostic factor, studies differed regarding the association of CLDN18.2 with worsened or improved prognosis. One study reported an association of CLDN18.2 expression with programmed death-ligand 1 expression. The use of different antibodies and definitions of CLDN18.2 positivity in patients with advanced G/GEJ adenocarcinoma poses a challenge for drawing definitive conclusions on the prognostic value of CLDN18.2 and association of CLDN18.2 with patient/disease characteristics. Additional research using a standardized approach to assess CLDN18.2 expression is needed.